The Effect of Total Third Party Fund and Number of Offices on Sharia Commercial Bank Financing - Supiah Ningsih; Rudy Irwansyah (Budapest International Research and Critics University, 2021)
This study aims to determine whether there is a significant influence between the amount of third party funds and the number of offices on Islamic Commercial Bank financing, and how much effect between the amount of third party funds on Islamic Commercial Bank financing and between the number of offices on Islamic Commercial Bank financing. The research design used is a quantitative research design using multiple linear regression analysis techniques supported by classical assumption tests and hypothesis testing with the help of the SPSS version 19 program. The samples of this study are the amount of third party funds, number of offices, and financing of Islamic Commercial Banks from January 2018 to December 2020. The results showed that simultaneously or simultaneously the amount of third party funds and the number of offices had a significant and positive effect on Islamic Commercial Bank financing based on the F test where Fcount > Ftable (265,455 > 3,28), while the significant level was 0,000 < 0,05. Partially, the factors that significantly effect the financing of Islamic Commercial Banks are the factor of the amount of third party funds where tcount > ttable (16,821 > 2,032) and the significance is 0,000 < 0,05. While the variable number of offices has a significance of 0,114 > 0,05, and the value of t count < ttable (-1,625 < 2,032). This means that the variable number of offices does not have a significant effect on Islamic Commercial Bank financing. Variations in factors that affect the financing of Islamic Commercial Banks are explained by the independent variables, the amount of third party funds and the number of offices which together explain the effect of 94,1%. While the remaining 5,9% is explained by other variables not examined in this study.